Assessment of the effluent polishing plant using a ultrafiltration membrane installed at a palm oil mill - Abdul Hadi, Numan; Hawari, Yahaya; Ngatiman, Muzzammil; Jalani, Nor Faizah; Wahad, Noorshamsiana Abdul; Halim, Rohaya Mohamed (Oficyna Wydawnicza Politechniki Wrocławskiej, 2019)
Palm oil mills discharge raw effluent with high biochemical oxygen demand (BOD) of about 25 000 mg O2/dm3. Conventional effluent treatment system uses ponds with a long hydraulic retention time of about 55–85 days, but the reduction of BOD is usually halted at 100–250 mg O2/dm3. Further reduction of BOD to below 20 mg O2/dm3 to meet regulation requirement needs further advanced treatment. This study evaluates the efficiency of an effluent polishing plant installed at a palm oil mill targeting final effluent BOD below 20 mg O2/dm3. Characteristic of the incoming and treated effluent, dissolved oxygen in the aeration ponds and the effluent flow rate of the treatment plant have been determined. Due to low process throughput at the mill, the polishing plant operated at only 60% of its designed capacity. Treatment of effluent showed reduction of BOD from 39.3±5.8 to 6.1±3.8 mg O2/dm3, i.e., a reduction by 80–94%. Colour – a newly proposed regulation parameter – was reduced from 1081±69 to 845±60 ADMI, i.e., by 11–30%. This study indicates that while the treatment of effluent to reduce the BOD to below 20 mg O2/dm3 is feasible, reduction of colour to less than 100 ADMI is not achievable.
Environment Protection Engineering. Vol. 45, 2019, nr 1, s. 155-170
Keywords: ochrona środowiska; inżynieria środowiska